Controlling of silicon-insulator-metal junction by organic semiconductor polymer thin film - Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2010)
Electrical and photovoltaic properties of a metal-semiconductor-insulator-polymer-metal diode were investigated. The n-Si/SiO(2)/MEH-PPV/Al diode shows a rectifying behavior with the rectification ratio of 2.22 x 10(5) at +/-5V and exhibits a non-ideal behavior due to the series resistance and oxide-organic layers. The organic semiconductor makes a contribution to the I-V characteristics of the diode and the trap-charge limited space charge and space charge limited current mechanisms were observed for the diode. The current-voltage characteristics of the n-Si/SiO(2)/MEH-PPV/Al diode under different illumination intensities give an open circuit voltage (V(oc)) along with a short circuit current (I(sc)). This suggests that the n-Si/SiO(2)/MEH-PPV/Al diode is a photovoltaic device with V(oc) = 0.456 V and J(sc) = 7.89 x 10(-8) A/cm(2) values under 100 mW/cm(2) illumination intensity. The photoconductivity mechanism of the diode is controlled by monomolecular recombination. The interface state density D(it) values with time constant tau(it) of the diode under dark and illumination conditions were found to be 2.53 x 10(10) eV(-1) cm(-2) with 5.09 x 10(-5) s and 2.50 x 10(10) eV(-1) cm(-2) with 8.27 x 10(-5)s, respectively. The obtained results indicate that the n-Si/SiO(2)/MEH-PPV/Al diode is a photo-sensitive diode. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Metal-oxide-semiconductor contact; Light sensitive capacitor; Organic semiconductor